2004
DOI: 10.1161/01.atv.0000145980.39477.a9
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Clopidogrel

Abstract: Abstract-Aspirin and the thienopyridines ticlopidine and clopidogrel are antiplatelet agents that display good antithrombotic activity. In the past few years, the concept of aspirin resistance has been largely emphasized in the medical literature, although its definition is still uncertain. I suggest that "aspirin-resistant" should be considered as a description for those individuals in whom aspirin fails to inhibit thromboxane A 2 production, irrespective of the results of unspecific tests of platelet functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(145 citation statements)
references
References 99 publications
5
133
0
3
Order By: Relevance
“…It is well known that pharmacologic inhibition of P2Y 12 with the thienopyriridine compounds ticlopidine and clopidogrel has a very good antithrombotic effect in patients at risk of cardiovascular or cerebrovascular disease [15,16]. In some clinical trials, the antithrombotic effect of these drugs proved to be superior, albeit marginally, to that of aspirin [33,34], despite the fact that thienopyridines do not adequately inhibit their pharmacological target in a relatively high percentage of treated patients [16], as opposed to aspirin, which adequately inhibits the activity of cyclooxygenase-1 (COX-1), which is its pharamacologic target [16], in the vast majority of treated patients [35][36][37]. We hypothesize that potentiation of the antiplatelet effect of PGI 2 in vivo may substantially contribute to the good antithrombotic effect of thienopyridines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that pharmacologic inhibition of P2Y 12 with the thienopyriridine compounds ticlopidine and clopidogrel has a very good antithrombotic effect in patients at risk of cardiovascular or cerebrovascular disease [15,16]. In some clinical trials, the antithrombotic effect of these drugs proved to be superior, albeit marginally, to that of aspirin [33,34], despite the fact that thienopyridines do not adequately inhibit their pharmacological target in a relatively high percentage of treated patients [16], as opposed to aspirin, which adequately inhibits the activity of cyclooxygenase-1 (COX-1), which is its pharamacologic target [16], in the vast majority of treated patients [35][36][37]. We hypothesize that potentiation of the antiplatelet effect of PGI 2 in vivo may substantially contribute to the good antithrombotic effect of thienopyridines.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, P2Y 12 is the target of potent antithrombotic drugs: its irreversible inhibition by the thienopyridine drugs ticlopidine or clopidogrel effectively reduces the incidence of cardiovascular events in patients at risk [15,16]. New, promising anti-P2Y 12 drugs, such as the thienopyridine prasugrel and the direct, reversible P2Y 12 antagonists cangrelor and AZD6140, are currently under clinical development [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The H2 haplotype was more frequent among 184 patients with peripheral artery disease than in 330 age-matched control subjects (OR, 2.3; CI, 1.4-3.9; p= 0.002 after adjustment for diabetes, smoking, hypertension, hypercholesterolemia, and other selected platelet receptor gene polymorphisms) [51]. Several studies tested the hypothesis that common polymorphisms of the P2Y 12 gene might interfere with the antiplatelet effects of drugs inhibiting the P2Y 12 receptor, accounting for the well known individual variability in the response to these agents [52,53]. The vast majority of these studies, with few exceptions, reported that P2Y 12 polymorphisms are not associated with altered platelet function inhibition by P2Y 12 antagonists [54][55][56][57][58][59][60][61].…”
Section: Treatmentmentioning
confidence: 99%
“…The optimal time to assess for toxicity after clopidogrel overdose has not been established [28]. The time required for metabolism of this prodrug to its active metabolite, which is responsible for antiaggregating activity, varies greatly in the population.…”
Section: Adp Antagonistsmentioning
confidence: 99%
“…The parent compound can be detected in the serum for up to 12 hours post-therapeutic ingestion, while its principal inactive metabolite can be detected up to 48 hours [30]. There is great interindividual variation in both the plasma concentrations of the active metabolite and the degree of inhibition of platelet aggregation produced by ADP [28]. Furthermore, because 50% of patients consuming clopidogrel have less than 30% relative inhibition of ADP-induced platelet aggregation [31], interpretation of laboratory tests following clopidogrel overdose is significantly limited.…”
Section: Adp Antagonistsmentioning
confidence: 99%